Identifikasi Keluhan Nyeri Bahu dengan Skala SPADI Pada Lansia Di Upt Pelayanan Sosial Tresna Werdha Jombang Kediri - cahyadinata, indra; Fatma Hardini, Kurniani; Noha Zulkarnain, Alfian; Hasanah, Maulida; Nabila, Aisya; Kurnia Maulidiani, Annisa (Fakultas Sains, Teknologi, dan Analsisi Institut ilmu Kesehatan Bhakti Wiyata, 2025)
Musculoskeletal disorders frequently arise from repetitive movements and prolonged static loading of muscles, which can result in pathological changes to joints, ligaments, and tendons. Contributing factors such as poor posture, mechanical load, frequency and duration of activity, and the surrounding work environment significantly increase the risk of musculoskeletal pain, including shoulder discomfort. Individuals experiencing shoulder pain require appropriate therapeutic intervention to support the healing process and prevent further functional impairment. This study aimed to identify upper extremity disorders in elderly individuals by utilizing the Shoulder Pain and Disability Index (SPADI) at the Tresna Wredha Social Service Unit in Jombang, Kediri. A descriptive quantitative method was employed through a two-phase approach: initial anamnesis and the administration of structured questionnaires to detect upper limb complaints, followed by specific physical examinations on the affected joint segments. A total of 20 elderly respondents participated in this study. The validity and reliability of the SPADI instrument were evaluated using Pearson's correlation coefficient and Cronbach’s Alpha. The results indicated that the SPADI scale is a valid and reliable tool for assessing both shoulder pain and functional limitations, as evidenced by correlation values exceeding the minimum validity threshold (Pearson’s r > 0.497) and a reliability coefficient of 0.657, surpassing the accepted minimum standard of 0.6. In conclusion, the SPADI instrument demonstrates strong psychometric properties and is effective in identifying shoulder pain and functional disability among elderly individuals. It offers a practical assessment tool for early detection of musculoskeletal disorders within social care settings.